Migration and Refugee Affairs: Role of Constitutional Court in Poland, Hungary, the Czech Republic, Slovakia, Serbia, Croatia, Slovenia and Romania - Oręziak, Bartłomiej (Migration and Central Europe: Challenges and Legal Responses, 2024)
The chapter highlights the roles of national constitutional courts in Poland, Hungary, the Czech Republic, Slovakia, Serbia, Croatia, Slovenia, and Romania. A national constitutional court exists in these countries in accordance with the supreme law regulations. The common denominator is that each national constitutional court has the power to a) assess the compatibility of lower-level legislation with higher-level legal regulations, specifically with the supreme law in a given country (constitution, fundamental law, etc.) and b) derogate or repeal, and sometimes temporarily suspend, in part or whole, legal norms declared unconstitutional. Aside from certain differences, these competencies seem to be a shared standard across all the analysed states. Additionally, in each state analysed, some regulations within the supreme law are about migration and asylum. The combination of these regulations with the indicated powers of national constitutional courts potentially allows for strong influence on topics related to migration and asylum, at least theoretically. Therefore, this chapter examines the jurisprudence of the national constitutional courts in Poland, Hungary, the Czech Republic, Slovakia, Serbia, Croatia, Slovenia, and Romania. The primary insights from this jurisprudence were presented and examined in terms of the power of position and image of position. This served as the basis for proposing an original methodology to assign a specific role to each national constitutional court and then to make an assignment.Keywords: constitutional law, migration, asylum, sovereignty, constitutional courts, comparative law.